2014
DOI: 10.1177/1098612x14549214
|View full text |Cite
|
Sign up to set email alerts
|

Sedative, hematologic and hemostatic effects of dexmedetomidine–butorphanol alone or in combination with ketamine in cats

Abstract: Acute stress induced by physical restraint can interfere with the validity of laboratory findings. Sedation could minimize such stress. However, it is not known whether sedation can affect hematologic and hemostatic parameters in cats. The purpose of this study was to evaluate hematologic and hemostatic parameters in domestic cats subjected to physical restraint in addition to one of two sedation protocols. In total, 50 cats were subjected to physical restraint and were then randomly divided into two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Several clinical studies support the use of butorphanol in cats. [32][33][34][35][36][37][38][39] Butorphanol has a rapid and relatively short duration of action with a suggested analgesic effect between 45 mins and 4 h. 40 One study reported a duration of 165 mins by use of the thermal threshold method in healthy cats. 41 Pathways for thermal stimuli may, however, differ from stimuli from a surgical wound, which is why conclusions about duration of analgesic effect on surgical pain should be made cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies support the use of butorphanol in cats. [32][33][34][35][36][37][38][39] Butorphanol has a rapid and relatively short duration of action with a suggested analgesic effect between 45 mins and 4 h. 40 One study reported a duration of 165 mins by use of the thermal threshold method in healthy cats. 41 Pathways for thermal stimuli may, however, differ from stimuli from a surgical wound, which is why conclusions about duration of analgesic effect on surgical pain should be made cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…However, sedation scores were not different when compared with dexmedetomidine-butorphanol alone. 69 Dexmedetomidine combinations usually decrease ejection fraction and fractional shortening, and increase end-diastolic and end-systolic volume in cats. This may affect the interpretation of echocardiography results.…”
Section: Jfms Clinical Practice 1039mentioning
confidence: 97%
“…However, sedation scores were not different when compared with dexmedetomidine–butorphanol alone. 69…”
Section: Drug Protocols For Feline Psa: An Evidence-based Approachmentioning
confidence: 99%
“…Several studies have reported the feasibility of different drug combinations and the effects induced by anesthetics on clinical parameters, particularly on the cardio-respiratory system [ 3 , 5 , 6 ]; in this regard, several studies have investigated the potential clinical and hematological alterations induced by sedation protocols in healthy cats, even though contradicting conclusions have sometimes been reported [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%